Career Support Programme to Expand Career Interests of Partners - Pardi, Pardi; Herdi, Herdi (Edukasi, 2024)
Students with special needs often face unique challenges in identifying and pursuing career paths that align with their abilities and interests. Previous studies have shown that tailored career guidance and vocational training can significantly enhance their career prospects and independence. This study explores the career interests of students with special needs at SMALB Pangudi Luhur, Jakarta, using the Strong Interest Inventory (SII) to identify interests across various fields such as STEM, Marketing, Sales and Services, Hospitality and Tourism, and Education and Training. The research, involving 30 students aged 17-21, reveals that many career options align with their visual abilities, while abstract and high-intelligence roles are less feasible. The findings highlight the need for tailored career guidance programs that include hands-on training and practical experiences to help these students understand and pursue suitable career paths. This study underscores the importance of vocational training and self-awareness in fostering career independence for students with special needs. It provides a basis for developing inclusive and culturally relevant career counseling programs.